PENINGKATAN KEMAMPUAN GURU SEKOLAH DASAR DALAM PENYUSUNAN INSTRUMEN RANAH SIKAP MELALUI IN HOUSE TRAINING - Astuti, Suhandi; Slameto, Slameto; Dwikurnaningsih, Yari (Universitas Kristen Satya Wacana, 2017)
This study departs from the issues of teacher skills gaps in Elementary School of Laboratorium Satya Wacana in arranging the instrument of attitudes assessment. This gap problems would be solved by school action research which aims to determine the steps of in-house training that can improve teachersâ skills in preparing attitudes instrument. The subjects of this study involved 15 primary school teachers of Elementary School of Laboratorium Satya Wacana. The research model that used was Stringer Model which consist of 3 aspects, namely : Look, Think, and Act. Instruments in this study were observation sheet and booklet. The data was analyzed quantitatively and qualitatively. The result showed: 1) The steps of in-house training that can improve teachersâ skills are planning, implementing, and evaluating in house training. On the steps of planning, activities of the formation of a committee, determine the trainer, participants, material and schedule. During the implementation phase carried out activities ranging from pretest, delivery and discussion materials and posttest. At this stage of the evaluation carried out assessments throughout the in house training activities; 2) In-house training can enhance teachersâ skills in arranging attitudes assessments during the learning process. The contribution of this research theoretically maintains the arranging steps of Likert assessment scale and practically improve teachersâ skills in arranging attitude assessment in teaching and learning process.